Addressing the Long COVID Crisis: Integrative Health and Long COVID - Alan Roth DO; Pan San Chan MD; Wayne Jonas MD (SAGE Publishing, 2021)
While COVID-19 has killed millions of people globally, its lasting effects on the health and well-being of entire populations are just becoming clear. As many as 30% of those diagnosed with COVID-19 report continuing health-related problems, regardless of the severity of the initial infection. Given the infection rate in the world, that translates to between 5.4 and 17.9 million globally; about 700 000 in the US. The syndrome goes by many names; here we call it "long COVID." Patients experience a wide range of symptoms, including serious organ system effects such as pulmonary fibrosis, myocarditis, new diabetes diagnoses, stroke, and other cerebrovascular events. They also experience ongoing pain, fatigue, and cognitive dysfunction. We suggest here that these patients require an integrative health approach, one that combines traditional medical management, non-pharmacological approaches, and behavior and lifestyle changes. Such an approach has been shown to be beneficial in other chronic illnesses such as fibromyalgia, chronic fatigue syndrome, and post-Lyme disease.